Vitamin D receptor and adipokine gene polymorphisms and risk of nasopharyngeal carcinoma among Malaysians - Sulong Abdul Rahman, Nurulassikin (2017)
Nasopharyngeal carcinoma (NPC) is a relatively rare malignancy in most parts of the world. However, NPC is a cancer which is common in Asia including Malaysia. NPC is the fourth most common cancer in Malaysia and shows highrates among the native people of Sarawak as well as the Chinese and the Malay populations. The distinctive racial/ethnic and geographic distribution of NPC worldwide suggests that both environmental factors and genetic traits contribute to its development. This study is aimed to conduct a molecular epidemiological study on single nucleotide polymorphisms (SNPs) of Vitamin-D receptor (VDR) and adipokine genes and risk of NPC among Malaysians. A matched case-control study was conducted in Hospital Kuala Lumpur (HKL) and Hospital Pulau Pinang (HPP). A total of 600 subjects consisting of 300 case patients and 300 controls were recruited in this study. Genomic DNA was extracted from blood and genotyped using polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) method. The genotype frequencies in case and control groups were estimated by direct gene counting from the gel images and analyzed using SPSS. There was no significant difference found in VDR BsmI, VDR TaqI, VDR ApaI, VDR FokI, IL6R Asp358Ala, LEPR Gln223Arg, ADIPOQ +45 T>G and PAI-1 4G/5G polymorphisms and risk of developing NPC between the NPC case and control subjects. The findings indicate that VDR and adipokine gene polymorphisms do not contribute as risk factors for NPC development among Malaysians. Further studies in a larger population must be carried out to reach a more reliable conclusion. However, there are three significant findings of two SNP interactions: VDR ApaI C/A and VDR TaqI T/C (OR=2.629); IL6R 358 Ala/Ala (variant) and LEPR 223 Arg/Arg (variant) (OR=2.085); and VDR ApaI C/A and IL6R 358 Ala/Ala (OR=3.817). Three out of five findings of three SNP interactions showed higher risks of NPC: VDR ApaI C/A, VDR TaqI T/C and LEPR Arg/Arg; IL6R 358 Asp/Ala, LEPR 223 Arg/Arg and VDR FokI T/C; and VDR BsmI A/G, VDR ApaI C/A and VDR FokI T/C with OR from 1.718 until 3.655. The other two results showed protective effects in NPC: LEPR 223 Gln/Arg, ADIPOQ +45 T/G and VDR FokI T/C; and LEPR 223 Arg/Arg, ADIPOQ +45 T/G and VDR FokI C/C with OR of 0.181 and 0.458, respectively. One of the three findings of 4 SNP interactions showed a higher risk of NPC: VDR BsmI A/G, VDR ApaI C/A, VDR FokI T/C and IL6R 358 Asp/Ala with OR=10.039. The other two results showed protective effects of NPC: LEPR 223 Gln/Arg, ADIPOQ +45 T/G, VDR FokI T/C and PAI-1 5G/4G; and LEPR 223 Arg/Arg, ADIPOQ +45 T/G, VDR FokI C/C and PAI-1 4G/4G with OR=0.147 and OR=0.193, respectively. In a survival analysis for LEPR Gln223Arg, Arg/Arg carriers had a higher overall survival time and better prognosis in NPC than those with Gln/Gln and Gln/Arg genotype carriers. This result suggests that the polymorphism LEPR Gln223Arg may be used as a molecular marker for progression and prognosis of NPC although more studies need to be conducted to achieve a more reliable conclusion due to controversial findings in other types of cancer.